2
$\begingroup$

I'm having a difficult time solving this integral. I tried integrating by parts:

$\int\sin^2x\cos4x\,dx$

$u=\sin^2x$, $dv=\cos4x\,dx$

I used the power reducing formula to evaluate $\sin^2x$

$du = 2\sin x\cos x\,dx$, $v=1/4\sin4x$

$uv - \int\ v\,du$

$\dfrac{1}{4}\sin^2x\sin4x - \dfrac{1}{2}\int\sin x\cos x\sin4x\,dx$

After this step, I tried evaluating the integral by using the $\sin a\sin b$ property.

$\dfrac{1}{4}\sin^2x\sin4x + \dfrac{1}{4}\int\cos x(\cos5x-\cos3x)\,dx$

$\endgroup$
  • $\begingroup$ I would use $\cos 4x = \cos^4 x - 6 \cos^2 x \sin^2 x + \sin^4 x$ $\endgroup$ – Doug M Jul 13 '16 at 21:15
2
$\begingroup$

$$\begin{align*} \sin^2 x \cos 4x &= \sin x (\sin x \cos 4x) \\ &= \frac{1}{2} \sin x (\sin 5x - \sin 3x) \\ &= \frac{1}{4}(\cos 4x - \cos 6x + \cos 4x - \cos 2x) \\ &= \frac{1}{2} \cos 4x - \frac{1}{4} \cos 6x - \frac{1}{4} \cos 2x. \end{align*}$$

Consequently, we immediately and rather trivially obtain $$\int \sin^2 x \cos 4x \, dx = \frac{1}{8} \sin 4x - \frac{1}{24} \sin 6x - \frac{1}{8} \sin 2x + C.$$


Alternatively, observe $$\begin{align*} \sin^2 x \cos 4x &= \sin^2 x (\cos 3x \cos x - \sin 3x \sin x) \\ &= \cos 3x \sin^2 x \cos x - \sin 3x \sin^3 x \\ &= \frac{1}{3} \left( \frac{d}{dx}\left[\sin^3 x\right] \cos 3x + \frac{d}{dx} \left[ \cos 3x \right] \sin^3 x \right) \\ &= \frac{1}{3} \frac{d}{dx}\left[\cos 3x \sin^3 x\right], \end{align*}$$ the last step due to the product rule applied to the functions $\sin^3 x$ and $\cos 3x$; thus $$\int \sin^2 x \cos 4x \, dx = \frac{1}{3} \cos 3x \sin^3 x + C.$$ It is quite straightforward to demonstrate that these antiderivatives are equivalent.

| cite | improve this answer | |
$\endgroup$
6
$\begingroup$

Hint: $\sin^2(x)\cos(4x)$ is an even function, hence it has a Fourier cosine series involving $\cos(nx)$ for $n\in\{0,1,2,3,4,5,6\}$. For any $n\in\mathbb{N}$, $$ \int \cos(nx)\,dx = C+\frac{\sin(nx)}{n}.$$ Actually: $$ \sin^2(x)\cos(4x) = -\frac{1}{4}\cos(2x)+\frac{1}{2}\cos(4x)-\frac{1}{4}\cos(6x).$$ Can you finish from here?

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

Use the fact that $ \cos 2x = \cos ^2 x - \sin^2 x = 1 - 2\sin^2 x $ , so $\sin^2 x = \frac{1 - \cos {2x}}{2}$

Replace it in your integral an it will get easy after spliting it into a few trivial. You will also have to use that $\cos\alpha\cos\beta=\frac{1}{2}[\cos(\alpha-\beta)+\cos(\alpha+\beta)]$

If you prefer to do this with partial integration , you could use the fact that $ \sin x \cos x = \frac{1}{2} \sin 2x $, and using $ \sin\alpha\cos\beta=\frac{1}{2}[\sin(\alpha+\beta)+\sin(\alpha-\beta)] $ you would also get two easy integrals.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Here is the most straight way to solve this problem:

Notice that $\cos 2x = \cos^2 x - \sin^2 x = 1 - 2 \sin^2 x $

So $\sin^2 x \cos 4x = \sin^2 (1-2\sin^2 2x) = \sin^2 [1-2(1-2\sin^2 x)^2] = -8\sin^6 x +8\sin^4 x -\sin^2 x$

By Reduction Formula: The integral can be easily solved.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Integrals of this sort can be done using some useful identities that are immediate corollaries of the angle-sum formulas $\cos A \cos B-\sin A \sin B=\cos (A+B)$ and $\sin A \cos B+\cos A \sin B=\sin (A+B),$ in conjunction with $\sin (-A)=-\sin A$ and $\cos (-A)=\cos A.$

We have $\cos (A+B)=\cos A \cos B -\sin A \sin B\;, $ and $\; \cos (A-B)=\cos A \cos B+\sin A \sin B.$ Adding these , we have $$\cos (A+B)+\cos (A-B)=2\cos A \cos B.$$ Subtracting them , we have $$\cos (A+B)-\cos (A-B)=-\sin A \sin B.$$ Similarly from the formulas for $\sin (A\pm B)$ we have $$\sin (A+B)+\sin (A-B)=2\sin A \cos B$$ and $$\sin (A+B)-\sin (A-B)=2\cos A \sin B.$$ From the angle-sum formulas, with $A=B$ and from $\cos^2A+\sin^2A=1,$ we have $$\sin^2 A=(1-\cos 2A)/2$$ and $$\cos^2 A=(1+\cos 2A)/2.$$ In particular $\sin^2 A \cos 4A=\frac {1}{2}(1-\cos 2A)\cos 4A=\frac {1}{2}(\cos 4A-\cos 2A\cos 4A)=\frac {1}{2}(\cos 4A-\frac {1}{2}(\cos 6A +\cos 2A)).$

For a lot more of this, see Trigonometry, by Hobson. (Dover Press re-print.)

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Use following trigonometric identities to solve this question,

$\sin^2x=(\frac{1-\cos2x}{2})$

& $\cos A\cos B=\frac{\cos(A+B)+\cos(A-B)}{2}$.

Given integration $$I=\int \sin^2x\cos 4x\ dx$$ $$put\ \sin^2x=\frac{1-\cos 2x}{2}$$ $$I=\int \Big(\frac{1-\cos 2x}{2}\Big)\cos 4x\ dx$$ $$\Rightarrow I= \frac{1}{2}\int \Big(\cos 4x-\cos 2x \cdot \cos 4x\Big)dx$$ $$\Rightarrow I=\frac{1}{2}\int\Big(\cos 4x-\frac{\cos(2x+4x)+\cos(2x-4x)}{2}\Big)dx$$ $$\Rightarrow I=\frac{1}{2}\int\Big(\cos 4x-\frac{\cos 6x+cos(-2x)} {2}\Big)dx$$ $$\Rightarrow I=\frac{1}{2}\int\Big(\cos 4x-\frac{\cos 6x+\cos2x} {2}\Big)dx\ \ \ \ \ \ \ \ \ \ \because \cos(-\theta)=\cos\theta$$ $$\Rightarrow I=\frac{1}{2}\int \cos 4x\ dx-\frac{1}{4}\int \cos 6x\ dx-\frac{1}{4}\int \cos 2x\ dx$$ $$\Rightarrow I=\frac{1}{2}×\frac{\sin 4x}{4}-\frac{1}{4}×\frac{\sin 6x}{6}-\frac{1}{4}×\frac{\sin 2x}{2}+c$$ $$\Rightarrow I=\frac{\sin 4x}{8}-\frac{\sin 6x}{24}-\frac{\sin 2x}{8}+c$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.